Regional lung function in scoliosis - Littler, W. A. (1972)
Radioactive xenon-133 was used to study the pattern of regional lung function in 35 scoliotic patients and 10 normal subjects in the sitting posture. The scoliotic curves were classified into three anatomical sites: high, if the apical vertebra was located between Th1 and Th5; mid, between Th6 and Th10; and low, between Th11 and L4; only the primary curve was considered and in 70% of the patients this measured more than 60°. The mean pattern of perfusion in patients with low and mid curves was not significantly different from that of the normals, nor was there any significant difference between the convex and concave lungs in these two groups. Patients with high curves showed three distinct patterns: [List: see text] The mean pattern of ventilation in the three groups of scoliotic patients was not significantly different from that of the normals although there was wide individual variation. The only patients to show a significantly abnormal ventilation/perfusion ratio were the high group. Regional lung volumes calculated from the equilibration scan indicated that in a majority of scoliotics the lung on the convex side of the curvature was larger than that on the concave side. Our results suggest that both the anatomical site and the angle of the scoliotic curvature have an effect on regional lung function but that this effect falls equally on the convex and concave lungs.